PENGEMBANGAN MODUL IPA BERBASIS MODEL EXPERIENTIAL LEARNING - Hidayati, Suci; Ahied, Mochammad; Hadi, Wiwin Puspita; Munawaroh, Fatimatul (Natural Science Education Research, 2023)
The purpose of this research was to got a product in the form of science module based experimental learning model on student concept understanding. The research used developing model ADDIE (analyze, design, development, implementation, evaluation). The sample in this research used students of VIII F grade SMP Negeri 1 Srengat by using of purposive technique sampling. Data collected used validation by validator, legibility, and student’s response. The result showed that there was: the validity of science module based on feasibility of material and media very worth used with of validity the material feasibility score was 90.58% and reliability score was 92.74%, while validity based on feasibility of media score was 95.07% and reliability score was 97.22. Based on the result can be concluded that the science module based on experiential learning model very feasibility used and used effective on learning.